Pathogenic effect of bunt wheat on male reproductive system in Mices. - Al-Taie, Mustafa A.K. (The Iraqi Journal of Veterinary Medicine, 2010)
This study was carried out to study the toxic effect of smut wheat on male reproductive system of mice. The experimental study was performed in the laboratory using 20 mice, which divided into two groups, one group feed on normal diet, the other fed on a mixture of 50% normal diet with 50% smut wheat. A histopathological study was done on the testes of Mice fed on smut wheat for 30 days. The histopathological study revealed thickness of basement membrane of semiriferous tubule of mice, and desquamation of the sertoli cells and spermatogonium from the basement membrane of seminiferous tubule and has adversely effect on male fertility.